Conference Speech Signal Annotation, Processing and Synthesis - Poznań, Poland 12-13 September 2006 - Demenko, Grażyna (Archives of Acoustics, 2006)
The conference Speech signal annotation, processing and synthesis, 11-13 September 2006 was organised by Department of Phonetics of Adam Mickiewicz University in Poznań, and Institut fur Kommunikationswissenschaften in Bonn as a part of German-Polish project supported by Alexander von Humboldt Stiftung. The conference was of interest to several scientific communities, including Speech Technologies, Linguistics, Phonetics, Audiology and Phoniatrics. Specially, its scientific program covered a wide variety of topics related to the contemporary state of art on Speech Signal Annotation, Processing and Synthesis. While the meeting was focused mainly on the fields of speech annotation for needs of processing and synthesis of speech signals, contributions from many other areas of speech and language studies have also been accepted. In order to support the multi-disciplinary goal of the conference, the international advisory committee included representatives of the different scientific communities. The conference was organised under auspices: The International Speech Communication Association - ISCA and Polish Phonetic Association (http://www.staff.amu.edu.pl/ fonetyka/) The scientific program included invited talks, presentations of papers in oral and poster sessions. Main scientific areas: segmental and suprasegmental speech annotation, databases in speech synthesis and recognition, talking conditions, applications of medical phonetics: speech signal analysis based medical diagnostics.